Bentuk dan Faktor Penyebab Hikikomori dalam Anime “Nhk Ni Youkoso!” - Maharani Patria Ratna; Yosafat Anugerah Mombong (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2021)
Hikikomori is one of the most common social problems in Japan. This research's object is the anime series NHK ni Youkoso !, with 24 episodes, which premiered from July to December 2006. The author uses the observation method of note-taking techniques to collect data, and the data analysis is written descriptively. The results of this study contained 11 forms of Hikikomori behaviour in the anime that the author studied, namely: hikikomori perpetrators confined themselves for more than six months, refused to interact with other people, refused to go to school, refused to leave the room, experienced hallucinations, experienced insomnia, professional setbacks, have thoughts of persecution, have feelings of depression, desire death and suicidal thoughts, and are addicted to alcohol. Meanwhile, the factors causing hikikomori behaviour are amae and the inability to accept intervention from others.